Mean platelet volume as short-term follow-up biomarker in children with celiac disease - Ramachandran, Mohanaraj; Agarwal, Anurag; Ravi, R N Mandal; Rajeshwari, K; Lomash, Avinash; Kapoor, Seema (Indian Journal of Child Health, 2017)
Objective: To assess the mean platelet volume (MPV) as a short-term follow-up biomarker in celiac disease (CD) and to compare it with anti-tissue transglutaminase antibody (TTGA) assay in Indian children. Material and Methods: Newly diagnosed 35 children aged